2015
DOI: 10.1371/journal.pone.0124555
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 and miR-200a, Revelation of New Possible Players in Modulation of Th17/Treg Differentiation and Pathogenesis of Multiple Sclerosis

Abstract: BackgroundOne of the main issues in pathogenesis of MS is Th17/Treg imbalance. There are growing interests in nominating miRNAs involved in Th17 cell differentiation, suggesting them as new therapeutic agents that may reduce progression of different autoimmune diseases specially MS.ObjectivesWe assessed transcript levels of miR-141 and miR-200a in MS patients, during relapsing and remitting phases. We also investigated possible role of miR-141, miR-200a in inducing differentiation to Th17 cells.Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs. However, miR-141 and Treg numbers were shown to fluctuate in relapsing and remitting phases of multiple sclerosis (Naghavian et al, 2015). In addition, miRNAs, such has miR-155, which regulate normal Treg development and function (Lu et al, 2009;Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013;Kohlhaas et al, 2009), were not found to be altered in the naïve CD4 T cells of patients with multiple sclerosis (Guerau-de-Arellano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs. However, miR-141 and Treg numbers were shown to fluctuate in relapsing and remitting phases of multiple sclerosis (Naghavian et al, 2015). In addition, miRNAs, such has miR-155, which regulate normal Treg development and function (Lu et al, 2009;Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013;Kohlhaas et al, 2009), were not found to be altered in the naïve CD4 T cells of patients with multiple sclerosis (Guerau-de-Arellano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some number of miRNA have been reported to modulate immune processes. Mir-26a-5p, mir-140-3p and mir-339-5p, for example, can inhibit NF-κB expression [4244]; and mir-185-5p and mir-200a-3p can regulate immune cell proliferation and differentiation [45, 46]. While to role of miRNAs has largely been studies in cells, miRNAs can also readily be found in the blood.…”
Section: Regulation Of Stress-induced Sterile Inflammation: Mirna Andmentioning
confidence: 99%
“…Efforts have been made in haematopoietic differentiation studies. MIR141 and MIR200A were identified as potential important miRNAs in the progression of multiple sclerosis through inducing differentiation of Th17 cells and inhibiting differentiation to Treg cells (Naghavian et al, 2015). MIR200B-3p regulates monocyte/macrophage differentiation by targeting p38IP (Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%